Analysis of Clinical Characteristics and Prognosis of Traumatic Brain Injury in Papua New Guinea. (1st December 2021) - Chen, Peng; Deng, Yongbing; Yu, Xing; Huang, Tao; Huang, Jingrui
Abstract : Objective . To evaluate the clinical characteristics and prognosis of TBI patients from 2016 to 2019 admitted to Port Moresby General Hospital (PMGH) of Papua New Guinea (PNG) and compare the results with previous researches to analyze current clinical characteristics and prognosis. Methods . A retrospective study was performed on 389 TBI patients in Port Moresby General Hospital (PMGH) over a 48-month period (from January 2016 to December 2019). The clinical and radiographic data were collected. Patients were followed up for at least 3 months, and outcomes were assessed using the Glasgow Outcome Scale (GOS). Univariate and multivariate logistic regressions were performed to analyze the prognosis and intracranial infection of patients, as well as the effect of surgery on the prognosis of TBI patients. Results . The average age of the 389 TBI patients was 24.9 years old, and the most common age was 18-40 years old, accounting for 55.5%. The proportion of male patients was 79.4%, and the proportion of juvenile patients (≤18 years) was 30.8%. The most primary cause of injury was fighting and brawling (38.0%). At admission, patients had an average GCS score of 9.1, and patients with severe TBI accounted for 46.8%. Overall, 32.1% of the patients had a good prognosis, with a mortality rate of 13.9% (54 cases). Analyzing the relationship between surgical treatment and prognosis in 303 patients with moderate or severe TBI, there was no statistical significance. Univariate and logistic regression analyses for poor prognosis included gender, GCS, multiple injuries, Rotterdam CT scores, and intracranial infection. Univariate and logistic regression analyses for intracranial infection included GCS, open brain trauma, and postoperative drainage time. Conclusion . Despite there has been a secular trend towards reduced incidence of TBI, the prognosis of moderate or severe TBI patients who received surgery showed no significant improvement, indicating that PNG, as a backward developing country, faced a huge problem in TBI prevention and control.